Nudging using the 'dish of the day' strategy does not work for plant‐based meals in a Danish sample of adolescent and older people. (29th January 2018) - dos Santos, Quenia; Nogueira, Bárbara Melo; Rodrigues, Vanessa Mello; Hartwell, Heather; Giboreau, Agnes; Monteleone, Erminio; Dinnella, Caterina; Perez‐Cueto, Federico Ja
Abstract: Adequate nutrition is an important factor for health and well‐being in adolescents and later years. Fruits and vegetables are part of a healthy diet as important source of nutrients, but their intakes are lower than the recommendations in European countries. This study aimed to compare the choices made by adolescents and older people between three similar dishes, one based on meat, one on fish and one on vegetables, in two different conditions: a neutral (control) situation and an intervention situation in which the vegetable‐based meal was designated 'dish of the day'. The comparisons of choices will be made within the same age group (adolescents in the control group vs. adolescents in the intervention group; older people in the control group vs. older people in the intervention group). A quasi‐randomised field trial design was used with a sample of 94 adolescents (aged 10–19 years) and 97 older people (aged ≥65 years), who were randomly allocated to intervention or control groups. In the control situation participants were asked to choose between three similar meals, one meat, one fish and one the VeggiEat dish. In the intervention, the VeggiEat dish was labelled the 'Dish of the day'. All dishes were provided free of charge, displayed side by side in the same order and served in same portions. The dish choices showed no differences between the control and intervention groups in both age groups, and no differences were found among the other variables analysed. This nudging strategy, 'dish of the day', seems not to work for the Danish sample of adolescents and older people. Future nudging studies with these populations are needed in order to find the best strategy to move adolescents' and older people's food habits toward a healthier pattern.